Validation Studies a Questionnaire Developed to Measure Incubator Business Technology Performance using PLS-SEM Approach - Fithri, Prima; Hasan, Alizar; Syafrizal, Syafrizal; Games, Donard (LPPM Universitas Andalas, 2024)
This research aims to collect data nationally using a questionnaire based on statements related to the performance factors of the Technology Business Incubator in Indonesia. This research uses the Structural Equation Modeling (SEM) method to test the validity and reliability of adapted scales. There are five stages starting with an outer model test to test the validity and reliability of the questionnaire's feasibility. The population in this research are organizations that are affiliated with the Indonesian Business Incubator Association (AIBI) and Ministry of Research, Technology and Higher Education, including business incubators belonging to ministries, local governments, the private sector and universities, there are 182 Technology Business Incubators in Indonesia. Testing in this research looks at whether the questions in the questionnaire are valid or not by going through two stages of convergent validity and discriminant validity. The first stage is convergent validity that aim of finding out the correlation between indicators and their latent variables. The second stage is discriminant validity which aims to find out whether the latent variable has adequate discriminant value and this was done to find out whether the statement items in the questionnaire were reliable and consistent in measuring the same symptoms in respondents. This research looks at the results of convergent validity analysis to consider the results of factor loading indicators on relevant factors, the results of testing the validity of all factors with a value greater than 0.50, one of which is an AVE value of 0.550, indicating that the indicators in these variables have a strong contribution in measuring the desired construct, and the reliability test of all variables is reliable because it exceeds 0.70, one of which is the facility variable which has a value of 0.858.